Intensi Pemanfaatan Aplikasi Mobile JKN di Masa Pandemi Covid 19 - Gusti Agung Sri Guntari (Pusat Riset dan Inovasi Nasional, 2023)
Every citizen has the right to guaranteed access to quality and affordable health services. Initially, all administrative matters related to JKN can be carried out at the BPJS Kesehatan office. However, the covid 19 pandemic situation requires people to limit social interactions to prevent the chain of transmission of covid 19 infection. Therefore, digital innovations such as the JKN mobile application are needed by the public, especially JKN participants. The JKN mobile application is an innovation developed to make it easier for participants who initially carried out administrative activities at the BPJS Kesehatan office, to switch to applications that can be accessed anytime and anywhere. This research is a qualitative research that aims to explore in depth how the use of the JKN mobile application, especially during the Covid-19 pandemic. The informants in this study consisted of 8 informants consisting of BPJS Kesehatan officers and 7 JKN participants who had used the JKN mobile application domiciled in Gianyar Regency, Bali. This study was conducted using the indepth interview method with purposive sampling technique. This research shows the results that the JKN mobile application is very helpful for participants in terms of checking or changing participant data, accessing contribution information and printing digital cards that can be used in health facilities. However, there are still many features that have not been utilized due to participants' ignorance of the existence of features such as online consultations and online queues. So that wider socialization is needed regarding the benefits of the JKN mobile application both on social media and electronic media.